Implementasi Pernyataan Standar Akuntansi Keuangan (PSAK) 69 Agrikultur pada Perum Perhutani Kesatuan Pemangku Hutan (KPH) Surakarta - Kurniawati, Dewi; falikhatun, falikhatun (Jurnal Akuntansi dan Bisnis, 2019)
The aims of this to determine the implementation of PSAK 69 Agriculture in Perhutani KPH Surakarta and its obstacles, and provide solutions to resolve these obstacles. This research is a qualitative research with interviews, observation, and documentation as data collection methods. The results of this study show that the implementation of PSAK 69 Agriculture is appropriate, overall, but there were differences in groups, presentation, and disclosure. Obstacles faced are difficult to determine the value of soil fertility, there is no policy regarding the liability of plat assets and non-technical costs, doubtful accuracy in the calculation of increamental growth, and lack of staff competence regarding financial accounting especially PSAK 69 Agriculture. The solution is that collaboration with universities to measure the level of soil fertility, grouping of non-technical costs, routine socialization followed by joint discussion activities and financial accounting based training. For the further research is expected to confirm with experts so that more comprehensive knowledge is obtained. Penelitian bertujuan mengetahui implementasi PSAK 69 Agrikultur pada Perhutani KPH Surakarta dan kendalanya, serta memberikan solusi untuk mengatasinya. Penelitian merupakan penelitian kualitatif dengan metode pengumpulan data wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan secara keseluruhan implementasi PSAK 69 Agrikultur telah sesuai, tetapi terdapat perbedaan pengelompokkan, penyajian, dan pengungkapan. Kendala yang dihadapi yaitu sulit menentukan nilai kesuburan tanah, belum ada kebijakan mengenai pertanggungjawaban aset tanaman dan biaya nonteknis, diragukannya keakurasian perhitungan pertumbuhan riap, dan kurangnya kompetensi staf mengenai akuntansi keuangan terutama PSAK 69 Agrikultur. Solusi yang diusulkan adalah perlu kerjasama dengan perguruan tinggi untuk mengukur tingkat kesuburan tanah, pengelompokkan biaya-biaya nonteknis, sosialisasi rutin diikuti kegiatan diskusi bersama dan pelatihan berbasis akuntansi keuangan. Penelitian selanjutnya diharap melakukan konfirmasi dengan ahli sehingga didapatkan pengetahuan yang lebih komprehensif.